ACTUAL PROBLEMS OF MODERN STRATEGIC MANAGEMENT - A. Bulgakov (Вестник университета)
The article is devoted to actual problems of strategic management for post-industrial enterprises. The article gives a brief overview of the approaches of different schools on strategic management and lists the main problems of strategic management for post-industrial enterprises. The article offers an approach to strategic management, which consists in the consideration of non-isolated enterprise, i.e. the enterprise in collaboration with partners, and the interaction of the enterprise with the external environment and the relationship of the value of its assets with sustainable development and social responsibility of business are also examined.